THE IMPACT OF SOCIAL MEDIA MARKETING, PRICE PERCEPTION, AND MENU VARIETY ON STUDENTS' PURCHASE DECISIONS - Ermansyah, Ermansyah; Ramadayani, Vivi (International Journal of Business and Information Technology, 2026)
This study aims to analyze the influence of social media marketing, price perception, and menu variety on students’ purchasing decisions in Pekanbaru City. The research employed a quantitative explanatory design. The population consisted of university students in Pekanbaru who had previously made purchases, with a total sample of 120 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS software. The results indicate that social media marketing, price perception, and menu variety each have a positive and significant effect on purchasing decisions. Among the independent variables, menu variety has the most dominant influence. Simultaneously, the three variables significantly affect purchasing decisions, explaining 52.8% of the variance in the model. These findings highlight that effective digital marketing strategies, appropriate price perception aligned with students’ purchasing power, and innovative as well as diverse menu offerings are crucial factors in enhancing purchasing decisions within a competitive café industry